The journey of Universal Hybrid-pi model-from its inception to experimental validation and its impact on Analog Circuit Design. (September 2018) - Sharma, Bijay Kumar
Abstract: Author always arrived at inconsistent results by h-model and hybrid-pi model analysis. In 1981 low frequency Universal Hybrid-pi model was proposed as the correct small signal model of CE BJT. Looking for enhanced output impedance as predicted by proposed Model, variable latching was discovered in 1989. In the present paper, the output impedance of CE BJT current sources are measured experimentally and verified analytically and by PSpice Simulation using the three models namely conventional Hybrid-pi model, universal Hybrid –pi model and T-model. Universal Model gives the best fit with 5% margin of random error whereas conventional model systematically underestimates and T-model systematically overestimates. Hence the validation of proposed model is a definite advancement of frontiers of science. This in combination with an analytic result for predicting the latch-up of CE BJT will be used in Industrial Standards in future to capture variable latching phenomena in Computer-Aided-Design (CAD)of high speed Analog Circuits with variable drive conditions. Abstract : One sentence summary: Universal Hybrid-pi is the most comprehensive, realistic and accurate model of CE BJT with a high degree of correlation between model and hardware.